Intersubjectivity and co-constructed framings: students’ role-play talks in online English-speaking sessions - Li, Leslie Huishan (Frontiers in Psychology, 2025)
This study investigates how lower-level English language learners achieve and maintain intersubjectivity and navigate through co-constructed framings during context-embedded tasks such as improvised role-play. In language education settings, activities associated with interactions often reflect multi-layered participant orientations beyond mere linguistic execution. From the perspectives of ethnomethodology and conversation analysis, linguistic actions are effective only when they are intersubjectively understood: the complexity of an activity necessitates corresponding levels of intersubjectivity for smooth progression. A close examination of sequence development in role-play activities shows how intersubjectivity is preserved as interlocutors engage in aligning and affiliative moves to avoid potential disruptions and maximize mutual contributions. Interlocutors’ progressive inputs are integrated as intersubjectively sustained elements of ongoing interaction framings only when collaboratively developed by the participating parties. The analysis also addresses the impact of online communication tools, acknowledging their increasingly essential role in online teaching. The results suggest the need for a dynamic concept of ‘framing,’ replacing ‘frame,’ and recommend that conversation analysis should account for the multi-layered contexts of surrounding activities.